A genome-wide association study of asthma symptoms in Latin American children. Issue 1 (December 2015) - Costa, Gustavo; Dudbridge, Frank; Fiaccone, Rosemeire; da Silva, Thiago; Conceição, Jackson; Strina, Agostino; Figueiredo, Camila; Magalhães, Wagner; Rodrigues, Maira; Gouveia, Mateus; Kehdy, Fernanda; Horimoto, Andrea; et al.
Abstract Background Asthma is a chronic disease of the airways and, despite the advances in the knowledge of associated genetic regionsin recent years, their mechanisms have yet to be explored. Several genome-wide association studies have been carried out in recent years, but none of these have involved Latin American populations with a high level of miscegenation, as is seen in the Brazilian population. Methods 1246 children were recruited from a longitudinal cohort study in Salvador, Brazil. Asthma symptoms were identified in accordance with an International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Following quality control, 1 877 526 autosomal SNPs were tested for association with childhood asthma symptoms by logistic regression using an additive genetic model. We complemented the analysis with an estimate of the phenotypic variance explained by common genetic variants. Replications were investigated in independent Mexican and US Latino samples. Results Two chromosomal regions reached genome-wide significance level for childhood asthma symptoms: the 14q11 region flanking theDAD1 andOXA1L genes (rs1999071, MAF 0.32, OR 1.78, 95 % CI 1.45–2.18, p -value 2.83 × 10−8 ) and 15q22 region flanking theFOXB1 gene (rs10519031, MAF 0.04, OR 3.0, 95 % CI 2.02–4.49, p -value 6.68 × 10−8 and rs8029377, MAF 0.03, OR 2.49, 95 % CI 1.76–3.53, p -value 2.45 × 10−7 ). eQTL analysis suggests that rs1999071 regulates the expression ofOXA1L gene. However, the original findings were not replicated in the Mexican or US Latino samples. Conclusions We conclude that the 14q11 and 15q22 regions may be associated with asthma symptoms in childhood.